Nanowelding: Shape‐Controlled 3D Periodic Metal Nanostructures Fabricated via Nanowelding (Small 6/2018). Issue 6 (8th February 2018) - Zhao, Zhi‐Jun; Shin, Sang‐Ho; Choi, Dae‐Geun; Park, Sang‐Hu; Jeong, Jun‐Ho
Abstract : In article number 1703102, Sang‐Hu Park, Jun‐Ho Jeong, and co‐workers propose a new method for fabricating three‐dimensional (3D) metal nanostructures based on nanoimprint lithography, electron‐beam evaporation, and nanowelding. This method allows for the shape of the nanostructures to be controlled by adjusting the temperature for the nanowelding process. This nanowelding method will find wide use in several important applications, including the fabrication of 3D metal nanostructures, color displays, holographic imaging, information encoding, anti‐counterfeiting, and biosensors.